PSYCHOSOCIAL CONSEQUENCES OF THE COVID-19 PANDEMIC AMONG TEENAGERS WITH DIABETES - Cheng, Hooi Peng; Selveindran, Nalini M; Wong, Jeanne Sze Lyn; Nor, Lisa Mohamed; Hong, Janet Yeow Hua (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The management of teenagers with diabetes during the COVID-19 pandemic has become more challenging with the negative psychosocial impact brought upon by the pandemic. METHODOLOGY We embarked on a cross-sectional study to identify the factors influencing glycaemic control (HbA1c) among teenagers with diabetes during the COVID-19 pandemic. Interviews regarding lifestyle changes were conducted among teenagers with type 1 (T1DM) and type 2 diabetes mellitus (T2DM), followed by the administration of the Depression, Anxiety, and Stress Scale (DASS-21). RESULTS A total of 59 adolescents with T1DM (32 males, 54.2%) and 31 patients with T2DM (10 males, 32.3%) were recruited. Overall, the HbA1c worsened from 9.13% before the COVID-19 pandemic to 9.33% during the pandemic (p-value 0.039). Significant factors which negatively influenced glycaemic control were male sex, puberty, prolonged screen time, presence of symptoms of anxiety/stress, and T2DM. However, skipping breakfast, sleep adequacy and physical activity did not directly influence the HbA1c. About one-third of the participants suffered from some form of mental disturbance (31.1% of patients had depressive symptoms, 38.9% of patients had anxiety symptoms, and 23.3% of patients experienced stress). The incidence of depression was higher among participants with T2DM, while anxiety and stress were higher among those with T1DM. Male gender, good glycaemic control pre-pandemic, and prepubertal status were associated with depressive symptoms during the pandemic. CONCLUSION Besides the disruption of daily routine, glycaemic control worsened among diabetic adolescents during the COVID-19 pandemic. A holistic management plan is needed to address the psychosocial concerns of this group to ensure optimal mental well-being and appropriate glycaemic control.